Classification of Malignant and Benign Skin Lesions Using CNN Models (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Dermatology has been transformed through the use of machine learning in health research. By leveraging large data sets and training deep learning models on diverse skin lesion images, researchers have opened the door to improving and modernizing traditional diagnostic methods. This paper aimed to develop a highly effective model for accurately classifying skin cancer images as benign or malignant, thus contributing to early detection. The methodology involved utilizing three custom Convolutional Neural Networks (CNNs) to extract essential features from dermatoscopic images, focusing on characteristics such as the borders of melanoma. Non-cancerous tumors are typically smooth and regular in their edges, while malignant ones have an uneven and rough border. The CNN models were trained on a melanoma dataset comprising images from both benign and malignant cases. Pre- processing steps such as data augmentation were also employed to further improve the performance of the model. The performance of the models was evaluated thoroughly using metrics such as precision, recall, F1 score, and accuracy. By training the models on Melanoma skin cancer, the models provided relatively high accuracies on the validations: 91%, 88%, and 94% for the first, second, and third model, respectively. Additionally, the accuracy for Benign skin cancer is 92%, 89% and 95% for the first, second, and third model, respectively. The third CNN model achieved the best precision and recall with 93% and 95% for Benign skin cancer, and 92% and 94% for Melanoma skin cancer. The third CNN model consistently outperformed the others, offering balanced and superior accuracy in distinguishing between benign and malignant skin cancer cases